Numerical Compliance with EU Fiscal Rules: Facts and Figures from a New Database - Martin Larch; Janis Malzubris; Stefano Santacroce (Intereconomics, 2023)
EU fiscal rules are meant to keep public finances on a sustainable path. This paper presents a new database that tracks numerical compliance with the four main rules of the Stability and Growth Pact starting in 1998. Our assessment of numerical compliance abstracts from the many exceptions and elements of discretion allowed by the letter and the spirit of EU law. It focuses on the main course of action implied by the rules. Overall, our database points to a very mixed compliance record. On average - across countries, years and rules - budgetary policies of the EU member states are compliant in just over half of the cases with stark and persistent differences across countries. We also detect a distinct cyclical pattern of compliance, which sends false signals of safety in good times.
Keywords: C10; E61; E62; H30; H62; 330; European fiscal policy; public debt; budget planning; EU countries; Europäische Finanzpolitik; Öffentliche Schulden; Haushaltsplanung; EU-Staaten